Short-Circuit Current Analysis for DFIG Wind Farm Considering the Action of a Crowbar - Yan Hong Yuan; Feng Wu (Energies, 2018)
With the increasing capacity of wind farms integrated into the power grid, the short-circuit current analysis for wind farms becomes more and more important. Since the wind turbine is usually integrated into the power grid via power electronic devices, the “crowbar” is installed in the wind turbine to protect the power electronic devices and to improve the fault ride through capability. The impact of the crowbar has to be considered during the short-circuit current analysis for the wind farm. In order to fully analyze the short-circuit current characteristics of a wind farm, the short-circuit currents for a doubly-fed induction generator (DFIG) wind turbine under symmetrical and asymmetrical faults considering the crowbar action characteristic are derived firstly. Then the action situation of the crowbar of a DFIG wind turbine is studied and the action area curve is obtained. Taking the crowbar action, or not, as the grouping criterion, wind turbines in the wind farm are divided into two groups, and the wind farm is aggregated into two equivalent wind turbines. Using the equivalent model, the short-circuit current of a wind farm can be calculated accurately. Finally, simulations are performed in MATLAB/Simulink which is the commercial math software produced by the MathWorks company in Natick, Massachusetts, the United States to verify the proposed short-circuit current calculation method for the DFIG wind farm.